Literary England: A Tourism Destination for the US traveller - Ingram, Claire; Themistocleous, Christos; Rickly, Jillian M.; McCabe, Scott (My University, 2019)
The purpose of this paper is to examine the likelihood of US tourists visiting England to engage in literary tourism. The paper employs an inductive between-subjects experimental design and compares findings from two surveys: one targeting a General Sample (GS) of the US outbound market (GS, n=2033), and the other targeting a Literary Society Sample (LSS) based in the US (LSS, n=220). The above data is supplemented with interviews undertaken with key stakeholders in the US outbound market, mostly tour operators (n=8).
Keywords: Literary Tourism; Travel research